The hydrochemistry of the headwaters of the River Severn, Plynlimon - C. Neal; J. Wilkinson; M. Neal; M. Harrow; H. Wickham; L. Hill; C. Morfitt (Hydrology and Earth System Sciences, 1997)
Water quality data spanning 13 years and covering an extensive range of major, minor and trace elements in rain and stream waters at Plynlimon in mid Wales, are presented. Rainfall water chemistry is highly variable due to varying proportions of marine and pollutant derived constituents associated with patterns of atmospheric circulation. Stream waters, being composed of different proportions of waters from three chemically distinct sources at any one time (atmospheric deposition, the soil system and deeper groundwaters), are also chemically highly variable. For example, components predominantly derived from deposition such as chloride change only in response to sea-salt deposition episodes. Solutes associated with bedrock weathering such as calcium, magnesium, and alkalinity decrease with increasing flow, those associated with the upper soil layers such as aluminium, many transition metals, dissolved organic carbon and hydrogen ions increase with increasing flow. The nutrients (e.g. nitrate, boron, bromide and iodine) exhibit strong seasonal cycles associated with cycles of vegetation growth and decay. The changes in stream water chemistry resulting from tree harvesting in the Afon Hore catchment are shown to have run their course within a period of eight years. Nutrient increases in the first few years following the commencement of felling have returned to or fallen below pre-felling values. Aluminium changes are shown to be complicated by changes in nitrate and calcium. Aluminium concentrations initially increased and have fallen below their pre-felling value. Data for chloride suggest a reduction in capture of dry and mist deposition; this indicates the importance of understanding reduced deposition as a result of felling. Felling has also affected the soil micro-climate which experiences greater fluctuations in temperature and an increase in the concentration of constituents associated with organic matter. Input-output mass balance estimates show that atmospheric inputs of many constituents are retained strongly by the catchment (e.g. ammonium, phosphate, barium, boron, lead and iodine). In contrast, many of the transition elements as well as divalent base cations, aluminium and alkalinity show a net release from the catchment. Conservative constituents such as chloride and sodium show a net input-output balance.